Hubungan Tingkat Kesulitan Belajar Dengan Hasil Belajar Siswa Kelas Tinggi SD 6/75 Biru - Muhammad Irfan; Muhammad Amran; Asriadi Asriadi; Novitasari Muhajir (Phinisi Integration Review, 2022)
This study is a correlational study with a quantitative approach which aims to determine whether there is a relationship between learning difficulties and science learning outcomes for high-class students of SD Inpres 6/75 Biru, Bone Regency. The population in this study were all high school students of SD Inpres 6/75 Biru, Bone Regency, which were used as samples with a total of 81 students. The sample was selected using a non-probability sampling technique, namely a saturated sample. The data obtained from the questionnaire (questionnaire) in the form of a Likert scale and documentation were then analyzed descriptively and analyzed inferentially. Based on the results of descriptive statistical analysis, the results of the study of learning difficulties have an average of 94,28 and a percentage of 57% in the medium category, while the science learning outcomes have an average of 80,94 and a percentage of 72% in the medium category. Based on the results of inferential statistical analysis shows that the value of rcount (-0,221) is greater (>) than the value of rtable (0,219) at a significance level of 5%, thus H0 is rejected and H1 is accepted. The conclusion of this research is that there is a negative and significant relationship between learning difficulties and science learning outcomes for high grade students of SD Inpres 6/75 Biru, Bone Regency. Penelitian ini adalah penelitian korelasional dengan pendekatan kuantitatif yang bertujuan untuk mengetahui apakah ada hubungan antara kesulitan belajar dengan hasil belajar IPS siswa kelas tinggi SD Inpres 6/75 Biru Kabupaten Bone. Populasi dalam penelitian ini adalah seluruh siswa kelas tinggi SD Inpres 6/75 Biru Kabupaten Bone yang dijadikan sampel berjumlah 81 siswa. Sampel dipilih dengan teknik nonprobability sampling yakni sampel jenuh. Data yang diperoleh dari kuesioner (angket) berbentuk skala likert dan dokumentasi kemudian dianalisis secara deskriptif dan dianalisis secara inferensial. Berdasarkan hasil analisis statistik deskriptif diperoleh hasil penelitian kesulitan belajar memiliki rata-rata 94,28 dan persentase 57% dengan kategori sedang sedangkan hasil belajar IPS memiliki rata-rata 80,94 dan persentasi 72% dengan kategori sedang. Berdasarkan hasil analisis statistik inferensial menunjukkan bahwa nilai rhitung (-0,221) lebih besar (>) dari nilai rtabel (0,219) pada taraf signifikansi 5% dengan demikian H0 ditolak dan H1 diterima. Kesimpulan hasil penelitian ini yaitu terdapat hubungan yang negatif dan signifikan antara kesulitan belajar dengan hasil belajar IPS siswa kelas tinggi SD Inpres 6/75 Biru Kabupaten Bone.